A dimensão política do Serviço Social: um estudo do trabalho profissional com a União dos Movimentos de Moradia de São Paulo - Rossatto, Tuane Aline (2018)
The purpose of the present study is the political dimension of the Social Service profession, expressed in the work of professionals working with the Union of Housing Movements of São Paulo (UMM-SP), in Social Housing Programs (HIS), in the program My House My Life - Entities (PMCMV-E). UMM-SP is one of the oldest housing movements on the public scene and carries with it the history of struggle for access to housing in the city of São Paulo. The movement has among its flags of struggle urban reform, the right to city and self-management in housing production through popular participation and the organization and protagonism of workers in the struggle for rights and social changes. In addition to the defense of the construction of egalitarian cities, UMM-SP has historically claimed the recognition of social work in Housing of Social Interest (HIS) in Housing Policy. It also defends the possibility of working with professionals who share a world vision for the benefit of the workers. In this way, it works with multidisciplinary teams, within this scope are the social workers. The Social Service has an eminently political action, its trajectory is linked to the power struggle of the social classes. We defend here that, like all social activity, professional actions are crossed by a political dimension. The aim of the present study is to capture and analyze the political dimension of the professional work present in the daily work, it indicates, the need to problematize the expressions of the political dimension of the profession present in the daily professional work as a means of apprehending its determinations and with that to create strategies for a professional action linked to the ethical-political norms defended by the hegemonic project of the professional category. The hypothesis is that all professional action is crossed by the political dimension and can strengthen different professional projects and societal projects and also, contradictorily, both in the same action. The methodology of the research was based on the critical perspective and the studies of historical and dialectical materialism, involving scientific procedures: bibliographic research and qualitative research with professionals who work with UMM-SP. It also composes the procedures, the observation in the spaces of professional and academic insertion of the researcher and photographic records. The results of the study point to a significant power in the possibilities of materialization of the political ethical project of the profession from a professional insertion that establishes new contours between professional performance and the political struggle